INFLUENCE FREE CASH FLOW, FIRM SIZE AND LEVERAGE ON PROFIT MANAGEMENT IN PHARMACY COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE IN THE 2018-2021 PERIOD - SERI AMELISA KUSUMAWATI (Indragiri Research Center (ingreat), 2023)
This research aims to determine the effect Free Cash Flow, Firm Size and Leverage on Profit Management in Pharmaceutical Companies Listed on the Indonesian Stock Exchange for the 2018-2021 Period. The population in this research are pharmaceutical companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The sampling method used in this research is method purposive sampling In a 4 year period in 11 pharmaceutical companies, 44 company data samples were obtained. The analysis used in this research is quantitative analysis with the help of the SPSS analysis tool (Statistical Package Social Science). The results of the analysis in this study show that partially Free Cash Flow has an effect on Profit Management with a sig value of 0.041<0.05, partially Firm Size has no effect on Profit Management with a sig value of 0.730>0.05, partially Leverage has no effect on Profit Management with a sig value of 0.102>0.05, and simultaneously obtained F count 2.062 <F table 2.839 with a significant level of 0.121>0.05 indicating that Free Cash Flow, Firm Size and Leverage has no effect on earnings management. Coefficient of Determination (R2) in this study Free Cash Flow, Firm Size and Leverage has an influence on earnings management of 13.4%, while the rest is given by other variables not examined in this research. It can be concluded that this shows the size of free cash flow, firm size and leverage will not have an impact on companies that carry out earnings management.